2020
DOI: 10.1038/s41598-020-79237-7
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of isothermal nucleic acid point-of-care tests for human coronaviruses: A systematic review and meta-analysis

Abstract: Many recent studies reported coronavirus point-of-care tests (POCTs) based on isothermal amplification. However, the performances of these tests have not been systematically evaluated. Cochrane Handbook for Systematic Reviews of Diagnostic Test Accuracy was used as a guideline for conducting this systematic review. We searched peer-reviewed and preprint articles in PubMed, BioRxiv and MedRxiv up to 28 September 2020 to identify studies that provide data to calculate sensitivity, specificity and diagnostic odds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 92 publications
6
66
0
Order By: Relevance
“…Rapid identification of individuals with COVID-19 is critical to prevent transmission and ensure patients receive optimal care. In agreement with others, we report that the ID NOW™ COVID-19 assay has high specificity but low sensitivity for detecting SARS-CoV-2 in dry swabs [ 9 , 10 , 16 , 17 ]. We noted a percent positivity of 13.4% (46/343) which reflected COVID-19 infection dynamics occurring at the time the study was conducted, which was during the peak of the second pandemic wave in Ontario, Canada.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Rapid identification of individuals with COVID-19 is critical to prevent transmission and ensure patients receive optimal care. In agreement with others, we report that the ID NOW™ COVID-19 assay has high specificity but low sensitivity for detecting SARS-CoV-2 in dry swabs [ 9 , 10 , 16 , 17 ]. We noted a percent positivity of 13.4% (46/343) which reflected COVID-19 infection dynamics occurring at the time the study was conducted, which was during the peak of the second pandemic wave in Ontario, Canada.…”
Section: Discussionsupporting
confidence: 92%
“…The ID NOW™ COVID-19 assay (Abbott Diagnostics Inc, USA), is a rapid (<15 minutes) molecular in vitro diagnostic test that uses isothermal nucleic acid amplification technology to qualitatively detect SARS-CoV-2 viral RNA directly from nasal, throat or nasopharyngeal (NP) swabs [4] . To date, the assay has demonstrated variable performance, with reported sensitivities ranging from 45% to 94% [5] , [6] , [7] , [8] , [9] , [10] . A recent systematic review noted an average sensitivity of 76.8% (95% CI: 72.9-80.3%) and a specificity of 99.6% (95% CI: 98.4-99.9%) across 5 independent evaluations [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Some, such as the ELA CHEMSTRIP, demonstrated high clinical sensitivity, whereas others, such as the ATILA and NEOKIT tests, showed high clinical specificity. These data are in accordance with previous studies reporting lower diagnostic ability with respect to that of RT-qPCR methods for the detection of SARS-CoV-2 [ 26 , 27 , 28 ], although some previous reports have described analytical sensitivities similar to those of RT-PCR assays [ 29 , 30 ]. In this regard, most LAMP studies have shown that the diagnostic specificity is of less concern than the sensitivity [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The smartphone camera-based colorimetric assay also meets the common requirements and expectations of point-of-care tests: simplicity, portability, no elaborative manipulations with samples, low cost, no use of harmful reagents, etc. [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Additionally, it meets the requirements of thin layer detectors like paper biosensors [ 36 ].…”
Section: Discussionmentioning
confidence: 99%